Crony Capitalism and Corruption in the Middle East and North Africa - Fatih Kırşanlı (Journal of Economy Culture and Society)
This paper provides a perspective on the political economy of crony capitalism and corruption in Egypt, Libya, Tunisia, Syria, and Yemen, severely affected by the Arab Spring, to propose that these factors triggered the uprisings. The crony capitalism in Egypt shows military dominance and its conglomerates in various sectors. Tunisian capitalism was around President Ben Ali and his wife, Leïla Ben Ali, who controlled about 30-40% of the economy. In Syria, President Assad and his cousin Makhloufi’s families controlled 60% of the country’s GDP, whereas the Qaddafi family controlled the economic paradigm in Libya. Lastly, in Yemen, certain tribes, families, and acquittances of Saleh dominated the Yemeni economy. After the Arab protests, all of these countries changed their regimes except Syria, where the demonstrations ignited a civil war. However, the pre-existing powers continued their dominance, heavily in Egypt and partially in Libya and Yemen. The so-called successful example is Tunisia, which struggled with the democratic transition that hindered its systematic economic development. The analysis elucidates dominant state-class relations pre- and post-Arab Spring and stipulates the channels through which crony capitalism and corruption may be eliminated.